2019
DOI: 10.1002/hed.25482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment modality on chronic opioid use in patients with T1/T2 oropharyngeal cancer

Abstract: Background The effect of treatment modality on long‐term opioid dependence in patients with oropharyngeal cancer has not been reported. Methods A retrospective cohort of 122 patients with T1/T2 oropharyngeal cancer undergoing treatment was generated. Risk factors associated with chronic opioid use were investigated by univariate and multivariate analyses. Results The prevalence of chronic opioid use was 45.9%. On multivariate analysis, primary nonsurgical treatment (odds ratio [OR] 4.5, 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…Age was among the most significant factors influencing patients’ postoperative pain experience and risk of continued opioid use in this study. The association of younger age with higher prevalence of chronic opioid use has also been reported among oropharynx and oral cavity cancer patients treated with any modality, including surgery . The impact of age on pain and opioid use has not previously been well described among patients undergoing major head and neck reconstructive surgery but is highly relevant to clinical practice for several reasons.…”
Section: Discussionmentioning
confidence: 98%
“…Age was among the most significant factors influencing patients’ postoperative pain experience and risk of continued opioid use in this study. The association of younger age with higher prevalence of chronic opioid use has also been reported among oropharynx and oral cavity cancer patients treated with any modality, including surgery . The impact of age on pain and opioid use has not previously been well described among patients undergoing major head and neck reconstructive surgery but is highly relevant to clinical practice for several reasons.…”
Section: Discussionmentioning
confidence: 98%
“…In 122 patients with early-stage oropharyngeal cancer, primary nonsurgical treatment was independently associated with chronic opioid use after treatment completion. 12 Similarly, administration of adjuvant therapy has been associated with chronic opioid use in patients with oral cavity cancer. 7,11 Since most studies on this topic have been isolated to a single head and neck subsite or treatment modality, the objective of this study was to characterize the association of treatment modality on the prevalence of chronic opioid use in a large cohort of patients with head and neck cancer.…”
mentioning
confidence: 99%
“…A total of 134 studies were identified, with 7 retrospective studies [8][9][10][11][12][13][14] (32.3%) underwent surgery followed by adjuvant RT/CRT ( Table 1).…”
Section: J O U R N a L P R E -P R O O F Resultsmentioning
confidence: 99%